Myositis ossificans of the quadriceps femoris in a soccer player - Marques, JP (2015)
A young soccer player was diagnosed with myositis ossificans 6 weeks after a muscle strain in the right thigh. Radiographic and sonographic investigations initially helped to confirm diagnosis and later supported clinical improvement. We present our approach to the case and discuss pathophysiology, prevention and treatment of this rare condition.